Evaluating Kohlberg’s Theory in the Context of Indonesian Preschool Moral Learning - Arifiyanti, Nurul (Departemen Penelitian dan Pengembangan Perkumpulan Program Studi PAUD Indonesia, 2024)
Moral education in Indonesia has gained increased importance, particularly following the implementation of the Independent Curriculum by the Ministry of Education and Culture across all educational levels, including preschool. However, moral education has not received sufficient instructional focus in early childhood settings. Addressing this gap requires examining relevant theoretical frameworks, one of which is Lawrence Kohlberg’s theory of moral development. This study aims to assess the applicability of Kohlberg’s theory to the context of moral education in Indonesian preschools. Employing a literature review approach, the study finds that current practices in early childhood moral education in Indonesia do not fully align with the principles and stages proposed by Kohlberg. Although preschool-aged children are generally categorized in the pre-conventional stage of moral development according to Kohlberg, several aspects of his theory are not consistently reflected in the observed educational practices. The findings contribute to the discourse by offering a critical perspective on Kohlberg’s theory and its relevance to early childhood moral education in Indonesia—an area that remains underexplored in the literature.